2009
DOI: 10.1007/s10815-009-9376-9
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cell contact during oocyte maturation in mice regulates meiotic spindle positioning and enhances developmental competence

Abstract: Purpose To investigate the role of cumulus cell contact during oocyte maturation on meiotic spindle assembly and the acquisition of developmental competence. Methods Cumulus oocyte complexes isolated from mouse ovaries subjected to in vitro or in vivo maturation were analyzed by confocal microscopy with respect to oocyte somatic cell contacts and for their ability to develop after parthenogenic activation during embryo culture. Results Cell contact is maintained during maturation in vivo, predisposing oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 49 publications
(68 reference statements)
3
68
0
Order By: Relevance
“…Consistent with our results which showed a significant decrease of its expression, the GJA1 underexpression was suggested as a good marker of oocyte quality and successful pregnancy [57]. Interestingly, the CCs transzonal projections (TZP) structures based on actin filaments were recently shown to be intact in mouse CCs in vivo [73]. Based on these findings, selective regulation of cumulus-oocyte exchanges looks to occur through membrane cytoplasmic extensions mainly the transzonal projections (TZP) until ovulation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with our results which showed a significant decrease of its expression, the GJA1 underexpression was suggested as a good marker of oocyte quality and successful pregnancy [57]. Interestingly, the CCs transzonal projections (TZP) structures based on actin filaments were recently shown to be intact in mouse CCs in vivo [73]. Based on these findings, selective regulation of cumulus-oocyte exchanges looks to occur through membrane cytoplasmic extensions mainly the transzonal projections (TZP) until ovulation.…”
Section: Discussionsupporting
confidence: 88%
“…Its expression was also reported in granulosa cells of rat and bovine species [69,70]. Keeping in mind the fact that synaptic vesicles transport was also achieved via microfilament and microtubule networks [71] and that similar cytoskeleton structures were reported in the transzonal cytoplasmic projections between CCs and the oocyte [72][73][74][75], one can assume the involvement of neuronal genes and molecules/vesicles exchange in CCs-oocyte dialogue.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Specifically, drugs that disassemble the actin cytoskeleton may protect subunits and filaments from the adverse effects of temperature and CPAs allowing for the dynamic components to be reassembled following thawing and re-equilibration. Finally, we would propose that the sensitivity of the actin cytoskeleton demonstrated in this work infers that the actin targets are manifold and may have the overall effect of disengaging filament interactions at the oocyte cortex and chromatin as has been shown recently [28].…”
Section: Discussionsupporting
confidence: 59%
“…The GO ontology analysis shows that regulation of this process is important for oocyte developmental competence. It has been shown that cumulus cell contact with the oocyte during maturation regulates the spatial organization and function of the meiotic spindle through actin-dependent mechanisms to enhance oocyte quality and developmental competence [Barrett and Albertini 2010]. This illustrates the importance of cell adhesion molecules as well as actin filaments involved in cytoskeleton regulation.…”
Section: Discussionmentioning
confidence: 94%